Light trap, an effective component of integrated management of Tuta absoluta(Lepidoptera : Gelechiidae) on Tomato - V Sridhar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2018)
The effectiveness of mass trapping the moths of Tuta absoluta was evaluated using light traps in tomato polyhouse at ICAR-Indian Institute of Horticultural Research, Bengaluru during March - June, 2018. Various colours of light sources were evaluated for their efficacy in attracting the moths. Of different coloured light sources evaluated, yellow and white (bluish) were found relatively effective for attraction of the moths. The efficacy of mass trapping was further evaluated and incandescent yellow bulb of 60 W was found most efficient in attracting both sexes of Tuta moths. Thus light traps can be an effective tool for IPM of this pest on tomato, under polyhouse conditions.